2016
DOI: 10.1002/ajmg.a.38010
|View full text |Cite
|
Sign up to set email alerts
|

KMT2D p.Gln3575His segregating in a family with autosomal dominant choanal atresia strengthens the Kabuki/CHARGE connection

Abstract: Choanal atresia is rarely reported in Kabuki syndrome, but is a common feature of CHARGE syndrome. Otherwise, the two conditions have a number of overlapping features, and the molecular links between them have recently been elucidated. Here, we report a case of a mother and her two children who presented with congenital choanal atresia. We performed whole exome sequencing on DNA from the mother and her two unaffected parents, and identified a de novo, novel variant in KMT2D. KMT2D p.Gln3575His segregated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
2
17
0
2
Order By: Relevance
“…In 2016, Badalato et al reported a mother, and her son and daughter with choanal atresia, hearing loss, and dental abnormalities, and who all harbor a missense variant (c.10725G>C p.(Gln3575His)) in KMT2D , which was de novo in the mother (Badalato et al, ). While their facial appearances were not typical for Kabuki syndrome, all three did have fetal fingertip pads, and the authors characterized these individuals as cases of “atypical Kabuki syndrome.” As noted by Sakata et al (), this variant is only eleven amino acids away from the variant found in Patient 4.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Badalato et al reported a mother, and her son and daughter with choanal atresia, hearing loss, and dental abnormalities, and who all harbor a missense variant (c.10725G>C p.(Gln3575His)) in KMT2D , which was de novo in the mother (Badalato et al, ). While their facial appearances were not typical for Kabuki syndrome, all three did have fetal fingertip pads, and the authors characterized these individuals as cases of “atypical Kabuki syndrome.” As noted by Sakata et al (), this variant is only eleven amino acids away from the variant found in Patient 4.…”
Section: Discussionmentioning
confidence: 99%
“…30 Molecularly, KMT2D and CHD7 both interact with members of the WAR complex 31 and clinical overlap between KMT2D variants and CHARGE syndrome has been previously postulated. 29,31 Two of these previous reports described individuals with clinical features that match those of the Ex38/39 KMT2D MVs cohort and that carry KMT2D missense variants, one with p. Gln3575His and another with p.Leu3564Val, that lie within the central conserved KMT2D region we describe. 29,32 We propose that these previously published individuals have neither KS1 nor CHARGE syndrome, and fit better with the condition that we describe in this study.…”
Section: Discussionmentioning
confidence: 61%
“…To experimentally test the functional impact of KMT2D missense variants, we generated FLAG-tagged versions of six KMT2D missense alleles: p.Leu3528Val, p.Leu3542Pro, p. Gly3553Val, p.Gln3575His, 29 p.Arg3582Trp, and p.Arg3582Gln. Fluorescence data revealed no changes in trimethylation H3K4 levels between all the missense variants tested in this assay compared with KMT2D normal control activity (Fig.…”
Section: Histone H3k4 Methylation Assaysmentioning
confidence: 99%
“…Otros diagnósticos diferenciales del síndrome de CHARGE son el síndrome de Kabuki, síndrome renalcoloboma, síndrome de Cat-Eye, síndrome de Joubert, síndrome Branquio-Oto-Renal, embriopatía secundaria a exposición a ácido retinoico y asociación VAC-TERL 10,11,17,18 .…”
Section: Figura 2 A)unclassified
“…Considerando la prevalencia descrita, (en Chile debiéramos tener 20 casos al año), creemos que hay una alta tasa de subdiagnóstico debido a la sobreposición de síntomas con otros síndromes y la alta morbimortalidad en periodo neonatal. Entre los diagnósticos diferenciales está el síndrome de microdeleción 22q11.2, síndrome de Kallman, síndrome de Kabuki, Treacher Collins, Mowat Wilson y síndrome 3M 10,11 .…”
Section: Introductionunclassified